The Activities of Informal Land Development Practices in Tudun Yan-Lihidda Settlement, Katsina State, Nigeria - Mustapha Muhammad (Indonesian Journal of Earth Sciences, 2022)
Failed policies, poor governance, corruption, inappropriate regulation, dysfunctional land markets, unresponsive financial systems and a fundamental lack of political interest and the limited capacity of the governance to provide adequate serviced land and housing for the majority of the ever- increasing urban population have attributed to the rapid development of informal settlements in many of our cities for the proper and effective management of our environment. It is noticed that the practice of informal land development in Katsina Metropolis largely dominated formal system of government. Problems such as irregular layout, inadequate accessibility, substandard plots size, congestion and lack of basic facilities and amenities etc. are attributed to the practice of informal land developments. This research involved physical and social survey which was performed in examining the location and group discussion and interview with residence and informal land developers to accessed some of the physical characteristics (i.e. house plot sizes, house development ratio area and road, drainage and setback) and other facilities such as health, out-post, cemetery, refuge site through oral interview with the informal land developers of the area. Secondary data adopted was the published and unpublished sources (i.e. books, journals, thesis/projects, maps etc.) This research aimed at accessing the activities of informal land development of Tudun Yan-Lihidda in Katsina Metropolis. The objective is to evaluate some of the physical characteristics of the area and identified the problems. Possible recommendations on the identified problems were made for good living environment. Problems such as irregular layout, substandard plots size, congestion and lack of basic facilities are attributed to the problems of the practice of informal land developments. There is need for the immediate attention of the urban planning board to address such problems where necessary in the area.